IMPLEMENTASI METODE PERLAFASS TIPKAS DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN SANTRI DI PONDOK PESANTREN MODERN AL-AZHAR - Abd. Azis; Kasuwi Saiban; Umi Salamah (STKIP Subang, 2026)
Al-Azhar Modern Islamic Boarding School has a good tartil and tahfidz Al-Qur'an program. Al-Azhar Modern Islamic Boarding School develops a more effective and efficient Qur'an tahfidz program which then produces qualified students in terms of maintaining the memorization of the Qur'an with a method called PERLAFASS TIPKAS and the Islamic Boarding School continues to make improvements and developments related to this method. The purpose of this study includes two things, namely: 1) To describe and analyze the implementation of the PERLAFASS method in the Al-Azhar Modern Islamic Boarding School. 2) Analyze and describe the implications of the implementation of the PERLAFASS TIPKAS method in the Al-Azhar Modern Islamic Boarding School. This research uses a qualitative approach with a case study type of research. The results of the study show that: 1) The implementation of the PERLAFASS TIPKAS method as a whole is carried out through four stages, namely: a) Planning which includes goals, competencies and skills, characteristics of the students, classroom design, learning materials and targets, learning design, time, facilities, and assessment; b) Implementation, including learning steps and classroom management; c) Controlling, including monitoring, reinforcement and adjustments; d) Evaluation, including technical and results.